Development and characterization of potato starch/lactucin/nano-TiO2 food packaging for sustained prevention of mealworms. (September 2022) - Wang, Yue; Zhang, Haitian; Zeng, Yuanbo; Hossen, Md Alomgir; Dai, Jianwu; Li, Suqing; Liu, Yaowen; Qin, Wen
Abstract: In this study, a novel composite film based on potato starch (PS)/lactucin (LT)/nano-TiO2 was prepared using the casting method. Scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction, Fourier-transform infrared spectroscopy, and differential scanning calorimetry were used to study the structure and morphology of the composite films. An ideal coordinated elastic and plastic mechanical behavior was obtained for this composite film at a 2 wt% LT content. The PS/2LT/3TiO2 composite films showed the lowest water vapor permeability at 1.42 ± 0.02 (10 −12 ·g·m/s·m 2 ·Pa) and exhibited good optical and antibacterial properties. Meanwhile, the transmittance values of all other PS/LT/TiO2 ternary composite films were approximately 0% at 220–360 nm. The highest inhibitory rate against both microorganisms was exhibited by the PS/4LT/5TiO2 film (92.67% ± 2.78%). Finally, the anti-mealworm study for of PS/4LT/3TiO2 revealed that 80% effective repellent activity was achieved against insects at 60 h. Collectively, these findings suggest that the PS/LT/TiO2 composite has potential for food anti-insect packaging and could serve to inform the design of alternative food packaging materials. Highlights: Potato starch/lactucin/TiO2 composite films were prepared by the casting method. The composite film displayed the lowest water vapor permeability (1.42 ± 0.02 gm/sm2Pa). Potato starch/lactucin/TiO2 films shown 80% effective repellent activity after 60 h. The composite film has potential use as a food anti-mealworm packaging.